2017
DOI: 10.1063/1.4986166
|View full text |Cite
|
Sign up to set email alerts
|

Impact of dispersion forces on the atomic structure of a prototypical network-forming disordered system: The case of liquid GeSe2

Abstract: A set of structural properties of liquid GeSe are calculated by using first-principles molecular dynamics and including, for the first time, van der Waals dispersion forces. None of the numerous atomic-scale simulations performed in the past on this prototypical disordered network-forming material had ever accounted for dispersion forces in the expression of the total energy. For this purpose, we employed either the Grimme-D2 or the maximally localized Wannier function scheme. We assessed the impact of dispers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1

Relationship

6
1

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 60 publications
1
18
0
Order By: Relevance
“…In this case the electronic structure, obtained within the selected DFT-GGA (generalized gradient approximation) framework, is used to compute the maximally localized Wannier functions (MLWF) on which the van der Waals scheme is based. 1 Considering liquid GeSe 2 , we found that the MLWF approach reproduces existing first-principles atomic structures while the vdW G one is less performing in the case of the Ge-Ge pair correlation function (Lampin et al, 2017). Turning to glassy GeSe 4 and glassy GeS 4 , the two vdW approaches were found to agree to a large extent, exceptions again occurring for some moderate differences in the intensity of the peaks in the Ge-Ge pair correlation function (Chaker et al, 2018b).…”
Section: Introductionmentioning
confidence: 81%
See 3 more Smart Citations
“…In this case the electronic structure, obtained within the selected DFT-GGA (generalized gradient approximation) framework, is used to compute the maximally localized Wannier functions (MLWF) on which the van der Waals scheme is based. 1 Considering liquid GeSe 2 , we found that the MLWF approach reproduces existing first-principles atomic structures while the vdW G one is less performing in the case of the Ge-Ge pair correlation function (Lampin et al, 2017). Turning to glassy GeSe 4 and glassy GeS 4 , the two vdW approaches were found to agree to a large extent, exceptions again occurring for some moderate differences in the intensity of the peaks in the Ge-Ge pair correlation function (Chaker et al, 2018b).…”
Section: Introductionmentioning
confidence: 81%
“…For the treatment of the core-valence interactions, we adopted a norm-conserving pseudo-potential according to the description of Troullier and Martins (1991). A plane wave basis set is chosen for the representation of the valence electrons with a corresponding energy cutoff of 40 Ry (Bouzid et al, 2015a,b;Lampin et al, 2017). The Brillouin zone integration is restricted to the Ŵ point.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A surprising effect was observed when using the Grimme approach. Indeed, the partial pair correlation functions (see figure 11) and the Ge-Se-Ge bond angle distribution did feature some additional contribution, in apparent disagreement with the MLWF and no vdW FPMD [64].…”
Section: The Structure Of Glassy Gete 4 and The Role Of Dispersion Fomentioning
confidence: 96%